Virtualization of open-source secure web services to support data exchange in a pediatric critical care research network. (21st March 2015) - Frey, Lewis J; Sward, Katherine A; Newth, Christopher JL; Khemani, Robinder G; Cryer, Martin E; Thelen, Julie L; Enriquez, Rene; Shaoyu, Su; Pollack, Murray M; Harrison, Rick E; Meert, Kathleen L; Berg, Robert A; et al.
Abstract: Objectives To examine the feasibility of deploying a virtual web service for sharing data within a research network, and to evaluate the impact on data consistency and quality. Material and Methods Virtual machines (VMs) encapsulated an open-source, semantically and syntactically interoperable secure web service infrastructure along with a shadow database. The VMs were deployed to 8 Collaborative Pediatric Critical Care Research Network Clinical Centers. Results Virtual web services could be deployed in hours. The interoperability of the web services reduced format misalignment from 56% to 1% and demonstrated that 99% of the data consistently transferred using the data dictionary and 1% needed human curation. Conclusions Use of virtualized open-source secure web service technology could enable direct electronic abstraction of data from hospital databases for research purposes.